Determination of total antioxidant status (TAS) as a biochemical parameter in control of workers' health - Jozanov-Stankov Olga; Đurić Jovanka; Dobutović Branislava; Isenović Esma R. (Archives of Biological Sciences, 2009)
Despite its importance for human health, the capacity of the antioxidative defense system (AOS) is still not included among regular biochemical analyses. In this study, we estimated the blood plasma level of the total antioxidant status (TAS) as an appropriate parameter for AOS monitoring with the aim of including it among other biochemical parameters in the regular control of health of the working population. We have applied a method developed by Randox Laboratories (England) that can be routinely performed on automatic chemical analyzers. The TAS level, in correlation with corresponding biochemical parameters, could contribute to better evaluation of the health of individuals and the working population.